EKSISTENSI SERIKAT PEKERJA/SERIKAT BURUH SEBAGAI SUBJEK HUKUM DALAM LINGKUP HUKUM KETENAGAKERJAAN INDONESIA - Nindry Sulistya Widiastiani (Fakultas Hukum Universitas Riau, 2021)
This article aims to review about the existence of Labour Union as legal person according to Indonesian Labour Law. The article uses normative legal research method, which are based on statute approach and conceptual approach. The conclusion of the article shows that The Labour Union could be categorized as a legal person, because it could hold rights and obligations. Also, it could be called as a rechtpersoon. It fulfilled the charactetistics and requirements as legal person and rechtpersoon, although Indonesian Labour Law/Regulation does not explicitly stipulate that.